Criminal justice - Haugen, David M. (Opposing viewpoints series, 2009)
Why consider opposing viewpoints? -- Introduction -- Does the criminal justice system need reform? -- Chapter preface -- 1) Grand juries should be reformed to check prosecutor power / Stanley S. Arkin -- 2) Grand juries should be reformed to reflect the communities they serve / Kevin K. Washburn -- 3) Law enforcement should cease racial profiling / Jesselyn McCurdy -- 4) Law enforcement does not engage in racial profiling / Steve Chapman -- 5) Terrorism suspects should be tried in federal court / Carl Tobias -- 6) Terrorism suspects should be tried by military commission / R. Peter Masterton -- 7) The criminal justice system should be lenient on minors / MacArthur Foundation -- Periodical bibliography -- What is the state of the prison system in the United States? -- Chapter preface -- High incarceration rates decrease crime rates / James Q. Wilson -- High incarceration rates do not necessarily decrease crime rates / Howard N. Snyder and Jeanne B. Stinchcomb -- Comprehensive reentry programs will reduce recidivism / Mark A. Nadler -- Reentry programs are often flawed / Douglas B. Marlowe -- Faith-based prison programs should be supported by the government / John D. Hewitt -- Faith-based prison programs are unconstitutional / Lawrence T. Jablecki -- Periodical bibliography -- Should sentencing laws be reformed? -- Chapter preface -- Mandatory minimum sentences are necessary and just / Alberto Gonzales -- Mandatory minimum sentences are unnecessary and unjust / Mary Price -- The death penalty should be abolished / Amnesty International -- The death penalty should not be abolished / David B. Muhlhausen -- Crack-cocaine sentencing laws should be reformed retroactively / Mark Mauer -- Crack-cocaine sentencing laws should not be reformed retroactively / Gretchen C.F. Shappert -- Periodical bibliography -- Are defendants' rights protected in the United States? -- Chapter preface -- 1) War detainees deserve the right to habeas corpus / Aziz Huq -- 2) War detainees have no right to habeas corpus / Andrew C. McCarthy -- Are we failing to safeguard the rights of poor defendants / Kirsten Anderberg -- 4) Judges are failing to safeguard the rights of poor defendants / Richard Klein -- 5) Circumventing police' knock and announce' rules violate civil rights / Radley Balko -- 6) The exclusionary rule should be abolished / William Tucker -- Periodical bibliography -- For further discussion -- Organizations to contact -- Bibliography of books -- Index